Magnetic vortex nucleation and annihilation in bi-stable ultra-small ferromagnetic particles. Issue 4 (15th January 2020) - Martínez-Pérez, M. J.; Müller, B.; Lin, J.; Rodriguez, L. A.; Snoeck, E.; Kleiner, R.; Sesé, J.; Koelle, D.
Abstract : We nucleate and manipulate magnetic vortices in ultrasmall magnetic nanoparticles and provide the full picture of their thermal and temporal stability. Abstract : Vortex-mediated magnetization reversal in individual ultra-small (∼100 nm) ferromagnetic particles at low temperatures is studied by nanoSQUID magnetometry. At zero applied bias field, the flux-closure magnetic state (vortex) and the quasi uniform configuration are bi-stable. This stems from the extremely small size of the nanoparticles that lies very close to the limit of single-domain formation. The analysis of the temperature-dependent (from 0.3 to 70 K) hysteresis of the magnetization allows us to infer the nature of the ground state magnetization configuration. The latter corresponds to a vortex state as also confirmed by electron holography experiments. Based on the simultaneous analysis of the vortex nucleation and annihilation data, we estimate the magnitude of the energy barriers separating the quasi single-domain and the vortex state and their field dependence. For this purpose, we use a modified power-law scaling of the energy barriers as a function of the applied bias field. These studies are essential to test the thermal and temporal stability of flux-closure states stabilized in ultra-small ferromagnets.